ANALISIS PROFITABILITAS PERUSAHAAN SEBELUM DAN SESUDAH CORPORATE REBRANDING (Studi Kasus Pada Kyriad Bumiminang Hotel Periode Juli – Desember 2015 dan Juli – Desember 2016) - Mulia, Putri Rahma; Kasmita, Kasmita; Abrian, Youmil (Journal of Home Economics and Tourism, 2017)
This research to analyze the profitability of Kyriad Bumiminang Hotel before and after corporate rebranding period July-December 2015 and July-December 2016 using five profitability ratios. This research is a descriptive research with comparative method. The data used in this research is secondary data. Technique of data collecting done by using method of documentation. The results of this research indicate that 1). Average PM Hotel Bumiminang before doing corporate rebranding 17.2% and after doing corporate rebranding 38.7%. There was an increase after a corporate rebranding of 21.5%. 2). Average ratio of OER Hotel Bumiminang before corporate rebranding 22.20% and after corporate rebranding 40.52%. There was an increase after the corporate rebranding of 18.32%. 3). Average ratio ROA Hotel Bumiminang before corporate rebranding 2.60% and after corporate rebranding 3.47%. There was an increase after the corporate rebranding of 0.87%. 4). Average ROE ratio of Hotel Bumiminang before corporate rebranding (18.60%) and after corporate rebranding of 16.72%. There was an increase after the corporate rebranding of 35.32%. 5) Average ratio GOPAR Hotel Bumiminang before corporate rebranding Rp. 100,346.8 and after corporate rebranding Rp.253.147,04. There was an increase after the corporate rebranding of Rp.152.800,7.Keywords: Analysis, Profitability, Corporate Rebranding.